Immunosuppression and Chagas disease; experience from a non-endemic country. (September 2015) - Salvador, F.; Sánchez-Montalvá, A.; Valerio, L.; Serre, N.; Roure, S.; Treviño, B.; Pou, D.; Sulleiro, E.; Bocanegra, C.; Molina, I.
Abstract: Reactivation of Chagas disease in the chronic phase may occur when immunosuppression is established, sometimes resulting in high parasitaemia and severe clinical manifestations such as meningitis and meningoencephalitis. Although this situation is being increasingly described, there is still scarce information. This retrospective observational study was performed in three Tropical Medicine Units of Barcelona (Spain) included in the International Health Programme of the Catalan Health Institute (PROSICS). The objective of the study was to describe epidemiological, clinical, microbiological, prognostic and therapeutic data from patients with Chagas disease and any kind of immunosuppressive condition attended in these three institutions from January 2007 to October 2014. From 1823 patients with Chagas disease attending these three centres during the study period, 38 (2%) had some kind of immunosuppressive condition: 12 patients had human immunodeficiency virus infection, 8 patients had neoplasia, 4 patients underwent organ transplantation and 14 patients had an autoimmune disease. Eight (21.1%) patients had cardiac involvement, and six (15.8%) patients had gastrointestinal involvement. Acute Trypanosoma cruzi infection was detected in two Spanish patients. Thirty-one (81.6%) patients received treatment with benznidazole, of whom 17 (54.8%) had some kind of adverse event. No patient had a severe manifestation or reactivation of Chagas disease. Patients with Chagas disease under immunosuppressive conditions are being increasingly described, especially in non-endemic countries. More information about this topic is required and international consensus in the diagnosis, treatment and follow up of these patients must be established to reduce the morbidity and mortality.